IMPACT OF PANELISTS ON WIBOR RATES – HYBRID APPROACH - Piotr Mielus (Polityki Europejskie, Finanse i Marketing)
The reform of financial benchmarks is one of the key elements of stability and trust in the financial market. In the money market, it is difficult to implement reforms because of the disappearance of the interbank deposit market, which was a reference market for IBOR-type rates. A solution is a hybrid method which combines declarations of panelists and prices of eligible transactions. Based on historic time series, the article analyses the impact of individual banks on the published index and presents the way the hybrid method can be used for WIBOR 3M. On the grounds of empirical data, the impact of particular banks was found to be moderate and the hybrid method proved to generate an interest rate series of a similar level, but of greater variance. The key problem is a limited impact of real-transaction prices on the published rate due to a low share of concluded deals and divergence of their prices from quotes generated by so called expert judgment in the analysed period.